Systematic review and meta-analysis of rates of clozapine-associated myocarditis and cardiomyopathy. (May 2020) - Siskind, Dan; Sidhu, Ashneet; Cross, John; Chua, Yee-Tat; Myles, Nicholas; Cohen, Dan; Kisely, Steve
Background: Clozapine is the most effective medication for treatment refractory schizophrenia, but is associated with cardiac adverse drug reactions. Myocarditis and cardiomyopathy are the most serious cardiac adverse drug reactions although reported rates of these conditions vary in the literature. We systematically reviewed and meta-analysed the event rates, the absolute death rates and case fatality rates of myocarditis and cardiomyopathy associated with clozapine. Methods: PubMed, EMBASE and PsycINFO were searched for studies that reported on the incidence of cardiomyopathy or myocarditis in people exposed to clozapine. Data were meta-analysed using a random effects model, with subgroup analysis on study size, time frame, region, quality, retrospective vs prospective, and diagnostic criteria of myocarditis or cardiomyopathy. Results: 28 studies of 258, 961 people exposed to clozapine were included. The event rate of myocarditis was 0.007 (95% confidence interval [CI] = [0.003, 0.016]), absolute death rate was 0.0004 (95% CI = [0.0002, 0.0009]) and case fatality rate was 0.127 (95% CI = [0.034, 0.377]). The cardiomyopathy event rate was 0.006 (95% CI = [0.002, 0.023]), absolute death rate was 0.0003 (95% CI = [0.0001, 0.0012]) and case fatality rate was 0.078 (95% CI = [0.018, 0.285]). Few included studies provided information on criteria for diagnosis of myocarditis and cardiomyopathy. Event rates of cardiomyopathy and myocarditis were higher in Australia. Conclusion: Clarity of diagnostic criteria for myocarditis remains a challenge. Observation bias may, in part, influence higher reported rates in Australia. Monitoring for myocarditis is warranted in the first 4 weeks, and treatment of comorbid metabolic syndrome and diabetes may reduce the risk of cardiomyopathy. The risks of myocarditis and cardiomyopathy are low and should not present a barrier to people with treatment refractory schizophrenia being offered a monitored trial of clozapine.